Gingerbread friends - Brett, Jan, 1949- (G.P. Putnam's Sons, 2008)
Lonely Gingerbread Baby, having set out to find a friend, enters a bakery where he tries to talk to different cookies and other figures, but winds up leading a crowd back to his house on a chase similar to the one in the familiar tale. Includes one fold-out illustration and a recipe for gingerbread cookies.